The Infallibility of the Papal Magisterium as Presented in the Pastoral Letters of the Bishops of the United States after Vatican I - Hennessy, Paul K. (Horizons, 1996)
Much of the confusion about the proper interpretation of the carefully formulated definition of Pastor Aeternus on the infallibility of the papal magisterium stems from improper presentations, even immediately after the Council. Only Archbishop Spalding of Baltimore took the time to nuance his presentation. The sympathy evoked worldwide among Catholics for the loss of the Papal States and the freedom of the Roman Pontiff also added to the confusion. The texts of the letters and statements of the bishops are important objects of study for anyone wishing to trace the course of "papal infallibility."